Revitalisasi konservasi tumbuhan obat keluarga (toga) guna meningkatkan kesehatan dan ekonomi keluarga mandiri di desa Contoh Lingkar Kampus IPB Darmaga Bogor - Agus Hikmat; Ervizal A.M. Zuhud; . Siswoyo; Edhi Sandra; Rita Kartika Sari (Institut Pertanian Bogor, 2011)
Medicinal plants and traditional medicine for along ago are important role in the health care, stamina maintain, and treat diseases. Therefore medicinal plants and traditional medicines have strong root in the part of community up to now. Research on revitalization of family medicinal plant (TOGA) conservation done at Kampong Pabuaran (Cibanteng village), and Kampong Gunung leutik ( Benteng village), results indicated that research locations have completely medicinal plants diversity for medicine all diseases of village communities mentioned. Number of medicinal plants found at Gunung Leutik and Pabuaran Sawah Kampong (Cibanteng and Benteng Villages) were 237 spesies, and 95 spesies often used by respondents mentioned villages. Species number of medicinal plants have potential to expand based on use value of these species treat main diseases of community villages Gunung Leutik and Pabuaran Sawah Villages (Benteng and Cibanteng) were 15 spesies, such as: sambiloto (Andrographis paniculata (Burm.F) Ness.), meniran (Phyl/anthus niruri L.), takokak (Solanum torvum L.), pegagan (Centella asiatica (L.) Urban.), temulawak (Curcuma xanthorrhiza Roxb.), jahe (Zingiber officinale-purpurea Rose.), jeruk nipis (Citrus aurantifolia (Christm & Panz) Swingle), binahong (Anredera cordifolia), mahkota dewa (Phaleria macrocarpus (Sheff). Boerl.), rosella (Hibiscus sabdariffa), pule pandak (Rauvolfia serpentine (L.) Benth. ex. Kurz.), sangitan (Sambucus javanica Reinw.), sirih (Piper betle L.), brotowali ( Tinospora crispa), and kenikir (Cosmos caudatus).